UPAYA GURU PPKn DALAM MENINGKATKAN TOLERANSI BERAGAMA DI SMA KUSUMA BANGSA PALEMBANG - Rizky Anisa Salsabila; Sri Artati Waluyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the efforts of Civics teachers in implementing inter-religious tolerance at Kusuma Bangsa High School Palembang. This research uses a qualitative approach with descriptive methods. Data collection techniques in this study used interviews, documentation, and observation techniques. The analysis techniques used in this study include data reduction, data presentation and conclusions. As a formal educational institution, schools are an important part of efforts to instil national character and religious guidance to students. Teachers as educators play an important role in efforts to instil an attitude of tolerance between religious communities in schools. Professional competent, and knowledgeable teachers not only act as teachers, but also educate, guide, direct, train, assess, and evaluate students. The things that the Pancasila and Civic Education teacher of Kusuma Bangsa Palembang High School does in improving the religious tolerance of students, namely modelling and fostering tolerance to students through habituation of praying in class and religious activities at school and fostering appreciation for differences through tolerance-based learning in accordance with the material taught.